Pathways and processes to adopting or switching to a single-dose HPV vaccination schedule in low- and middle-income countries: a qualitative study. - Sunny Roy; Megan D Wysong; Erica N Rosser; Ishani Sheth; Casey Geddes; Rupali J Limaye; Joseph G Rosen (PLOS Global Public Health)
The World Health Organization (WHO) recently endorsed a single-dose human papillomavirus vaccination (HPVV) schedule, but adoption of the revised immunization schedule has not been uniform, notably in low- and middle-income countries (LMICs) with outsized cervical cancer burdens. We sought to characterize the sequence of events, as well as actors/institutions involved, that facilitate or impede country-level decision-making related to the HPVV schedule. From September 2023 to February 2024, we conducted 66 semi-structured interviews with national immunization stakeholders from 19 LMICs in Africa and Asia, sampled purposively by the maturity of the HPVV program and HPVV schedule. Using purposive text analysis to synthesize emerging insights from interviews, we qualitatively discerned a sequence of decision-making pathways and processes, including actors involved at each stage of the decision-making continuum, related to adoption or switch to an HPVV single-dose schedule. We identified six key sequential steps LMICs follow when deciding on an HPV dosing schedule. Firstly, the new recommendation emerges where WHO and the Strategic Advisory Group of Experts (SAGE) release new HPV vaccine recommendations. Second, the information is shared with the Ministry of Health (MoH) and Expanded Programme for Immunization (EPI). The MoH is informed, and they convene a National Immunization Technical Advisory Group (NITAG) to assess the new HPV vaccine schedule recommendation. Third, there is the review and consideration of evidence. The NITAG reviews evidence on factors like cost-effectiveness, supply chain, disease burden, and anticipated vaccine hesitancy. Fourth, the NITAG deliberates, achieves consensus, and submits a recommendation to the MoH, which endorses the NITAG's recommendation or requests additional evidence/information before rendering a final decision on the immunization schedule. Fifth and finally, the Interagency Coordination Committee (ICC) reviews the MoH's recommendation and provides final authorization before changes to the HPV immunization schedule is communicated to Gavi.